Juridical Review of Money Laundering Crimes committed by the President Director of PT. Asabri - Sareng Purnomo; Bernat Panjaitan; Nimrot Siahaan (Journal of Social Research, 2022)
Background: This study aims to find out and analyze about the juridical review of money laundering crimes and find out and analyze about liability in cases of money laundering crimes committed by the president director of PT. ASABRI. Objective: This study aims to find out and analyze the juridical review of money laundering crimes and find out and analyze about liability in cases of money laundering crimes committed by the president director of PT. ASABRI. Methods: This research belongs to the normative type of research. So that it can be known that Dan the elements of not criminal money laundering are perpetrators, acts (financial or financial transactions) with the intention of hiding or disguising the origin of wealth from its illegitimate form (illegal) as if it were legal property. Results: Money Laundering as a crime has the characteristic that this crime is not a single crime but a double crime. The point is that the criminal act of money laundering is a form of crime committed either by a person and/or corporation by deliberately placing, transferring, spending, paying for the plunge, entrusting, taking out of the country, changing the form, exchanging for currency or securities or other acts of property that he knows or reasonably suspects is the result of non-criminal proceedings. Conslusion: Based on the explanation above, it can be concluded that the money laundering process has three stages, namely the Placement or placing Stage, the second is the Layering or Separating Stage, and the last is the Integration Stage or the use of wealth that has appeared legitimate. Keywords: Criminal Acts, Money Laundering, Asabri